2021
DOI: 10.3892/mmr.2021.12458
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR‑205‑5p alleviates the inflammatory response in allergic rhinitis by targeting B‑cell lymphoma 6

Abstract: allergic rhinitis (ar) is an ige-mediated upper airway disease with a high worldwide prevalence. Microrna (mir)-205-5p upregulation has been observed in ar; however, its role is poorly understood. The aim of the present study was to investigate the effect of mir-205-5p on AR-associated inflammation. To establish an AR model, BalB/c mice were sensitized using an intraperitoneal injection of ovalbumin (oVa) on days 0, 7 and 14, followed by intranasal challenge with oVa on days 21-27. a lentiviral sponge for mir-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…The results in our experiments suggested that increased miR-205-5P expression altered the levels of Th1/Th2 cytokines in OVA-induced AR, thereby affecting IgE production. Furthermore, it was reported that miR‑205‑5p knockdown improved AR by targeting BCL6 [ 12 ]. Based on the present study, miR‑205‑5p bound to 3UTR of PEBP1 and regulated its expression to involve in the pathogenesis of AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in our experiments suggested that increased miR-205-5P expression altered the levels of Th1/Th2 cytokines in OVA-induced AR, thereby affecting IgE production. Furthermore, it was reported that miR‑205‑5p knockdown improved AR by targeting BCL6 [ 12 ]. Based on the present study, miR‑205‑5p bound to 3UTR of PEBP1 and regulated its expression to involve in the pathogenesis of AR.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have noted that miRNA is associated with a variety of clinical diseases, including AR, chronic sinusitis, asthma, atopic dermatitis and other immune diseases [ 8–11 ]. A recent report demonstrated that miR‑205‑5p was involved in inflammatory response in AR with the help of B‑cell lymphoma 6 [ 12 ]. Previous research has found that PEBP1, also called RAF1 kinase inhibitory protein (RKIP1), can increase allergic responses in mast cells [ 13 ], indicating that PEBP1 was involved in AR.…”
Section: Introductionmentioning
confidence: 99%
“…Chen D found that BCL6 may have a negative regulatory effect on NLRP3 (nucleotide-binding oligomerization domain-like receptor family pyrin domain 3) by binding to it and attenuating inflammation in human renal tubular epithelial cells and in vivo [30] . Zhang S found that BCL6 can act as a target of mir-205-5p and mir-205-5p knockdown can reduce the inflammatory response in allergic rhinitis by targeting BCL6 [31] . Jager A found that Bcl6 has an important regulatory function in macrophages, limiting TLR-induced inflammatory responses [32] .…”
Section: Discussionmentioning
confidence: 99%
“…After the operation, the mice were bred normally for 90 d. After 90 d, the mice were euthanized through 150 mg/kg pentobarbital sodium and diagnosed as CRSsNP by pathological examination, and the nasal mucosal tissues were subsequently collected [ 12 ]. For lentivirus treatment, on the basis of the CRSsNP modeling, we administered 20 μ L lentiviruses to the mice intranasally on the 2 nd d after the operation [ 13 ], followed by the same steps as for the CRSsNP model establishment.…”
Section: Methodsmentioning
confidence: 99%